VD_FINDINFO HC / 2012 / 413 vom 22. Mai 2012 - VD Tribunal cantonal (2012)
RÉCUSATION | 6 par. 1 CEDH, 30 al. 1 Cst., 73 al. 1 LOJV, 18 al. 1 ROTC, 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH), 50 al. 2 CPC (CH), 8a al. 3 CDPJ, 8a al. 7 CDPJ